'You are Constantly Trying to Make the Best Out of All Situations': Adolescents with Overweight and School Health Nurses in Norway on Weight Stigma and Physical Activity. Issue 1 (2nd September 2022) - Skogen, Ingeborg Berg; Dahl, Silje Louise; Høydal, Kjetil Laurits
Background: Weight stigma is highly present in physical activities in the lives of adolescents with overweight. Nevertheless, increased physical activity is one of the target lifestyle determinants in health workers' follow-up with adolescents at risk of negative weight development. The present study examines how adolescents with overweight and school health nurses who monitor and guide these young people perceive weight stigma in physical activity. Methods: We interviewed a community sample of 10 adolescents (13–18 years) with overweight or obesity and six school health nurses about weight stigma in physical activity. Data were analysed using reflexive thematic analysis. Results: We generated three main themes describing experiences with weight stigma in physical activity. 1) 'being (in)visible' identified contradictory motives of both wanting to hide their body to avoid being on display and at the same time working hard to be physically active to disprove the stereotypical view of people with overweight, 2) 'being perceived as unacceptable' identified adolescents' understandings of themselves as individuals who ought to transform into a slimmer version through exercise and 3) 'dealing with social interaction' identified different strategies used to handle the stigma. Conclusion: Insight into adolescents' complex experiences with weight stigma related to physical activity and follow-up with school health nurses is essential to inform approaches to increase physical activity participation without reinforcing weight stigma.